A Review of Enabling Technologies Applied to Real Estate Pricing - Barbosa, Larissa Kelly da Silva França; Rabbani, Emilia Rahnemay Kohlman; lago, Eliane Maria Gorga; Cruz, Felipe Mendes da (National Journal of City Management, 2026)
Objective – To understand how enabling technologies have been applied to real estate pricing through a systematic literature review, mapping methods, applications, and trends in real estate appraisal engineering.Methodology – A Systematic Literature Review (SLR) was conducted following the PRISMA protocol. Searches were carried out in relevant databases such as Science Direct, Scopus, and Web of Science, using a search string with Boolean operators. A total of 55 articles published between 2014 and 2024 were analyzed.Originality/Relevance – This study systematizes scientific articles published over the last ten years on the use of emerging technologies in real estate appraisal, highlighting the contrast between traditional methods and new approaches based on artificial intelligence.Results – Most studies still rely on traditional valuation methods, but there is a growing use of enabling technologies such as machine learning and geoprocessing. China stands out as the country with the largest number of publications. Regarding applications, real estate investment studies predominate (49%), followed by urban planning. The application of artificial intelligence improves accuracy and reduces uncertainty in real estate decision-making.Theoretical/Methodological Contributions – The findings contribute to the theoretical advancement of real estate appraisal engineering and provide practical insights for developers, construction companies, public agencies, and market agents by pointing out promising methodological and technological trends for property value analysis.Social and Environmental Contributions – From a social perspective, improving accuracy in property valuation strengthens the information base for housing and urban public policies, allowing projects to be better aligned with the real needs of the population. From an environmental standpoint, studies that incorporate ecological variables foster sustainable urban planning, encourage the rational use of land, enhance the value of areas with green infrastructure, and contribute to reducing negative environmental impacts.
Keywords: Real Estate Appraisal; Enabling Technologies; Machine Learning; Real Estate Market; Pricing